An Exploration of the Use of Literature as a Therapeutic Intervention in Social Work. (9th January 2021) - Murphy, Jennifer; Jenkinson, Hilary
Abstract: In recent decades, a greater awareness and familiarity has developed in relation to incorporating creative approaches to working with individuals and groups within a social work context. Art therapy, music therapy and even drama therapy have become more commonplace within the range of approaches employed by agencies and practitioners working therapeutically. However, the use of literature as a therapeutic tool is perhaps a less well-known, less developed and under-researched area of practice. This article discusses the potential for literature to be used as a therapeutic tool and explores the power of words to enable us to make sense of our surroundings and experiences. The article also presents findings of a small-scale piece of research undertaken with practitioners currently using literature in their practice. Themes arising from this research are explored such as the potential of literature to facilitate reflection, practitioners' experiences of applying the approach, the value of engaging with literature in developing expressive language and the potential for this work in promoting inclusion.